A review of melting ice adaptation strategies in the glacier tourism context. Issue 2 (15th March 2021) - Salim, Emmanuel; Ravanel, Ludovic; Deline, Philip; Gauchon, Christophe
ABSTRACT: Globally, tourism is being deeply impacted by glacial retreat caused by climate change. However, research on stakeholders' adaptation to climatic change and its threat to the industry on tourism niche is currently inadequate. Thus, through a literature review of 61 glacier peer-reviewed papers, this paper highlights the advancement in research on glacier tourism and provides some basis for understanding stakeholders' adaptation strategies to climate change. The review shows that glacier tourism research publications increased between 2015 and 2020. It also identifies some impacts of climate change on the glacier tourism industry as well as 27 adaptation strategies to climatic change, which are classified under seven main themes: changes to access, activities, tourism planning, educational activities, temporal substitutions, spatial substitutions, and glacier shrinkage attenuation. We discuss the relevance of the resilience concept in the tourism industry and recommend that tourists' experiences should be enhanced by applying the findings of research on tourists' motivations and landscape perception and developing more adaptation-oriented research. The findings suggest that the glacier tourism industry can reduce its vulnerability to climate change through increased collaboration between tourism operators and climate and tourism researchers.